PENGARUH PELATIHAN TEKNOLOGI PESTISIDA LIMBAH TEMBAKAU TERHADAP PERILAKU PETANI - Pingkan Aditiawati; Mia Rosmiati; Dadang Sumardi (JURNAL AGRIBISNIS TERPADU, 2015)
The purpose of the training is to socialize and provide comprehension to farmers about technologyinnovation of botanical pesticide from tobacco waste. Farmer- behavior change is expected to lead tofarmers’ desire to apply technological innovation of botanical pesticide. This research useddescriptive method. Determination of respondent is conducted by a census of all the farmers whoattended training on botanical pesticide technology (20 respondents). Indicators of farmer- behaviorchanges including cognitive, affective, and psychomotor about the benefits, how to make and apply thebotanical pesticide. The indicators are measured using a Likert scale. Data were analyzed usingdescriptive statistics. The results showed that the training of botanical pesticide technology has a goodinfluence on the behavior of farmers.